Trigonometric approximation of functions in generalized Lebesgue spaces with variable exponent - Akgün, R. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We investigate the approximation properties of the trigonometric system in L_2π^p(·). We consider the fractional order moduli of smoothness and obtain direct, converse approximation theorems together with a constructive characterization of a Lipschitz-type class.